Governing abandoned land: Storylines on natural forest regrowth in France and Spain. Issue 135 (September 2022) - Frei, Theresa; Edou, Kim; Rodríguez Fernández-Blanco, Carmen; Winkel, Georg
Abstract: Natural forest regrowth on abandoned land represents a major land use change in some regions of Europe. This is driven by various factors related to land abandonment, particularly changing socioeconomic conditions for agriculture and rural depopulation. Little research exists about how the issue is addressed at the policy level. This paper looks into the policymaking related to natural forest regrowth in France and Spain, two countries where land abandonment and natural forest regrowth occur at significant scales. We conduct a policy discourse analysis building upon 27 interviews carried out between 2018 and 2020 with policy actors from various fields that connect with these topics. We find four competing storylines in both countries: extensive agriculture, forestry, landscape conservation, and wilderness. These storylines differ regarding the framing of natural forest regrowth as a problem or an opportunity, and the preferred policy solutions. While storylines rooted in extensive agriculture, landscape conservation and forestry tend to problematize the phenomenon, a wilderness storyline voices an opportunity perspective. In France, a few actors voice elements of an insignificance storyline. Given its spatial importance, natural forest regrowth will likely become more important for future policymaking in the EU. Engaging in further research across disciplines and policy fields is necessary to study the phenomenon and its possible management and governance options. Highlights: Policy actors narrate natural forest regrowth on abandoned land through storylines. Interview results distinguish four storylines on natural forest regrowth. Three storylines tend to highlight the threat of natural forest regrowth. Natural forest regrowth has not yet received much political attention. Shifts towards a rewilding perspective may strengthen an opportunity framing.